Analyzing the impact of the shadow economy on economic growth in Cambodia - Mong, Mara; Lim, Siphat (Edelweiss Applied Science and Technology, 2025)
A model of equations known as the VAR model has been employed to investigate the relationships among four endogenous variables: the growth rate of GDP, the shadow economy, the inflation rate, and final consumption expenditure. The initial response of GDP to shocks from the shadow economy is negative for the first three quarters, with the effect gradually decreasing from the fifth to the tenth quarter. In the first and second quarters, there is no observable impact on GDP due to shocks from the inflation rate; however, this shock becomes harmful between the third and fifth quarters before stabilizing and dissipating. The findings from the impulse response function suggest that GDP responds positively to changes in final consumption expenditure during the first two quarters, with the influence waning from the third quarter onward. Over the forecast horizon, the effect of the shadow economy on GDP variation is estimated to range from 3.38% to 6.11%, while the inflation rate's impact fluctuates between 0.06% and 5.05%, and final consumption expenditure contributes to changes between 0.31% and 0.34%. Furthermore, the analysis of forecast error variance decomposition throughout the projected period indicates that GDP variation is considerably influenced by the dynamics of the shadow economy, inflation rate, and consumption expenditure.